Evaluation of very high cycle fatigue zones in 42CrMo4 steel with plate-like alumina inclusions. (September 2019) - Seleznev, M.; Merson, E.; Weidner, A.; Biermann, H.
Graphical abstract: Highlights: Under fatigue load plate-like alumina inclusions behave similar to globular ones. Areal micro-roughness is calculated for each fatigue crack zone. "Smooth area" fatigue zone is experimentally defined between FGA and fisheye zone. Arrest marks can form on fatigue fracture under constant stress amplitude. Abstract: Quenched and nitrided 42CrMo4 specimens, treated by different reactive filters were tested in very high cycle fatigue regime using ultrasonic method. Despite total alumina reduction fatigue limit showed no improvement due to large alumina plates whose parameters were studied. Areal roughness of fatigue crack zones was measured by confocal laser scanning microscopy. Periodic arrest marks were studied and used for crack growth rate calculation. Smooth area was experimentally defined as a zone between fine granular area and fisheye by imaging, roughness minima, fixed Δ K = 6.4 and crack growth rate of ∼10 −10 m/cycle. Classification of internal crack zones is proposed.